Another Piece of the Puzzle: The Importance of Officer Characteristics and Group Processes in Understanding Post-stop Outcomes. (August 2019) - Tillyer, Rob; Smith, Michael; Lloyd, Caleb D.
Objectives: Investigate the potential relationship between officer characteristics and poststop outcomes during police–citizen encounters. Methods: Data on police-initiated contacts were drawn from a large, racially/ethnically mixed urban environment. Cross-classified, multilevel models were estimated to identify correlates of five poststop outcomes. Results: Officer gender, race/ethnicity, and length of service exerted a direct and/or moderating effect on the likelihood of a traffic citation, criminal citation, and a search. Conclusions: Officer characteristics are a key, yet understudied, component to understanding the complexities of police officer decision-making in police–citizen encounters. The results indicate a noticeable component of the variation in poststop outcomes rests at the officer level thereby substantiating the continued exploration of these relationships. Moreover, the moderating effect of officer characteristics on the relationship between minority citizens and poststop outcomes presents new potential directions for expanding the social conditioning model and offers evidence regarding the in-group versus out-group perspectives within the context of police–citizen interactions. Limitations include omitted variable bias and inexact measurement of some variables.